Antimicrobial Studies of some 1,1-Bis-[2-hydroxy-3-(3-Aryl-Prop-2-en1-one)-5-Methyl Phenyl] Methanes and Their Dibromo Derivatives - Kinhikar, R.V.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Some bis-chalcones and their bromo derivatives were synthesized and tested for antimicrobial ,activities against S. aureus, E. coli, Pr. mirabilis, Ps. aeruginosa, E. aerogenes, S. typhi and Pr. Vulgaris. The titled compounds were found effective against amost all micro-organisms,.